To solve the inequality \(25x^2 - x^4 \geq 0\), we can start by rewriting it:
\[ -x^4 + 25x^2 \geq 0 \]
This can be rearranged to:
\[ x^4 - 25x^2 \leq 0 \]
Next, we can factor the left-hand side:
\[ x^2(x^2 - 25) \leq 0 \]
We can factor further:
\[ x^2(x - 5)(x + 5) \leq 0 \]
Now we can analyze the expression \(x^2(x - 5)(x + 5)\). The zeros of the expression (the points where it equals zero) are \(x = 0\), \(x = 5\), and \(x = -5\).
These points split the number line into intervals. We need to test these intervals to determine where the expression is non-positive:
-
Interval: \( (-\infty, -5) \)
- Choose \( x = -6 \): \[ (-6)^2(-6 - 5)(-6 + 5) = 36 \cdot (-11) \cdot (-1) = 396 > 0 \] (Not included)
-
Interval: \( (-5, 0) \)
- Choose \( x = -1 \): \[ (-1)^2(-1 - 5)(-1 + 5) = 1 \cdot (-6) \cdot 4 = -24 < 0 \] (Included)
-
Interval: \( (0, 5) \)
- Choose \( x = 1 \): \[ (1)^2(1 - 5)(1 + 5) = 1 \cdot (-4) \cdot 6 = -24 < 0 \] (Included)
-
Interval: \( (5, \infty) \)
- Choose \( x = 6 \): \[ (6)^2(6 - 5)(6 + 5) = 36 \cdot 1 \cdot 11 = 396 > 0 \] (Not included)
Now, we include the points where the expression is equal to zero, which are \(x = -5\), \(x = 0\), and \(x = 5\).
Thus, the solution to the inequality \( 25x^2 - x^4 \geq 0 \) is:
\[ [-5, 0] \cup [0, 5] \]
Final Answer
B. The solutions are the values of \(x\) in the interval: \[ [-5, 0] \cup [0, 5] \]